Taxonomic diversity and eco-exergy changes in fishery resources associated with artificial reefs over 14 years in Daya Bay, China - Yuan, Huarong; Chen, Pimao; Li, Xiaoguo (Frontiers in Marine Science, 2022)
Marine habitat degradation resulting from human activities and environmental pollution has led to serious deterioration of marine fishery resources. To address this issue, countries worldwide are exploring sustainable fishery approaches. Installation of artificial reefs (AR) is rapidly increasing. AR have been widely constructed globally to conserve fishery resources and improve marine habitats. As an important biological group of marine fishery resources, nekton are widely evaluated to determine the effects of ecological restoration and resource conservation. In the current study, we compared the dynamic properties of taxonomic diversity and the eco-exergy of nekton community from 2 to 14 years after AR construction in Dalajia, China. The results indicated that the species number and density of nekton significantly increased after AR construction. Siganus oramin became an absolute dominant fish species in the reef area and its surroundings. The species diversity and evenness of the nekton community decreased, whereas species richness increased. The abundance, biomass, and eco-exergy of the nekton community increased over time because of the dominance of fishes. Our results highlight that AR can increase and conserve fishery resources, improve the structure of the nekton community, and increase ecosystem stability. But, at the same time, the dominance of S. oramin can interfere in the reef community. The explosive growth was quantitatively and qualitatively higher than that of other species, the diversity and evenness indices showed a decreasing trend, although the number of nekton species was significantly higher than that in the background survey and CA habitat during the same period.